Foreign direct investment, foreign remittances, foreign imports and economic growth: Evidence from Tunisia / Nurul Farrahin Liana Abd Jalil - Abd Jalil, Nurul Farrahin Liana (Faculty of Business and Management, 2018)
Economic growth is considered as one of the most important indicators of a healthy economy. One of the biggest effects of long-term growth of a country is that it has a positive effect on national income and the level of employment, which increases the standard of living. As the country's GDP is increasing, it is more productive, which leads to more people being employed. This increases the wealth of the country and also its population. Like all developed and developing countries, small and low middle income economies country like Tunisia is also striving hard to achieve and sustain the long run economic growth. However, most of the previous study have not provided consistence evidence in favour of a robust relationships between external determinants and economic growth. Therefore, further investigation of the significant relationship between external determinants and economic growth is indeed necessary. This study focus on analysing the external factors that could influence the economic growth in Tunisia proxies by their indices between the years 1978 to 2016. This study uses the collection of data from secondary data and the sample is based on annual data from year 1978 to 2016. All data is obtained from World Development Indicators. Other than that, this study expect that external factors such as foreign direct investment and foreign remittances will have significant and positive relationship towards economic growth in Tunisia while foreign imports will have adverse effect towards the economic growth of Tunisia.